A case report: emphysematous gastritis - C., Suwannachod; P., Rujitanon (International Surgery Journal, 2017)
Emphysematous Gastritis is a rare condition but high mortality rate. This condition usually occurs in an immunocompromised host. The computed tomography (CT) scan shows gas located within the gastric wall. Early recognition and aggressive management is important for survival of the patient. A 54-year-old man presented to emergency department with severe abdominal pain, vomiting, and diarrhea. Abdominal examination showed significant for epigastrium pain with rebound tenderness. The CT of upper abdomen showed abnormal extensive free air along the greater curve of stomach. Perforation of the stomach could not be excluded. The patient underwent for emergency exploratory laparotomy. Intraoperative finding found the anterior stomach wall, from the fundus to the body, appeared abnormal color and necrosis but no perforation. Esophagogastroduodenoscopy (EGD) showed marked swelling and some areas of necrosis of mucosa from the fundus to the body of stomach. No active bleeding or perforation site was found. Intraoperative saline irrigation was performed without gastric resection. Emphysematous gastritis is a rare condition of gastritis due to invasion of gas producing organisms. The CT abdomen with intravenous contrast shows the presence of air bubbles in the stomach wall. The role of endoscopy is to monitor severity and exclude other pathology. At this time, most of the reports suggest medical treatment better than surgical treatment in patient who has no complication. Medical treatment plays a major role in this case, instead of surgical treatment and the results appeared to be well improved accordingly.